1993
DOI: 10.1016/0735-1097(93)90756-q
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and significance of ventricular tachycardia and fibrillation in the absence of hypotension or heart failure in acute myocardial infarction treated with recombinant tissue-type plasminogen activator: Results from the thrombolysis in myocardial infarction (TIMI) phaes II trial

Abstract: Ventricular tachycardia and fibrillation are not markers for reperfusion after thrombolytic therapy. These arrhythmias are associated with occlusion, not patency, of the infarct-related artery. Early mortality is increased in patients who develop ventricular tachycardia and fibrillation, even in the absence of congestive heart failure and hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 32 publications
4
22
1
1
Order By: Relevance
“…Importantly, it shows that although the occurrence of VT/VF during primary angioplasty is associated with a greater length of stay, it does not have an impact on the procedural success or risk of adverse in-hospital and long-term outcomes. Thus, our study findings are in contrast to those of large trials evaluating VT/VF in patients with STEMI receiving thrombolytic therapy, which have reported a higher incidence of up to 20% and a greater risk of adverse short-and long-term outcomes with this arrhythmia (1)(2)(3)(4)(5)(6). Previous studies have shown that the size of myocardial infarction not only correlates with an increased incidence of VT/VF, but is also an important predictor of mortality in patients with STEMI (5,6,16 -18).…”
Section: Findings Of the Present Studycontrasting
confidence: 84%
See 2 more Smart Citations
“…Importantly, it shows that although the occurrence of VT/VF during primary angioplasty is associated with a greater length of stay, it does not have an impact on the procedural success or risk of adverse in-hospital and long-term outcomes. Thus, our study findings are in contrast to those of large trials evaluating VT/VF in patients with STEMI receiving thrombolytic therapy, which have reported a higher incidence of up to 20% and a greater risk of adverse short-and long-term outcomes with this arrhythmia (1)(2)(3)(4)(5)(6). Previous studies have shown that the size of myocardial infarction not only correlates with an increased incidence of VT/VF, but is also an important predictor of mortality in patients with STEMI (5,6,16 -18).…”
Section: Findings Of the Present Studycontrasting
confidence: 84%
“…Some of these investigations have suggested that these ventricular arrhythmias are associated with coronary reperfusion, although others have related them to suboptimal reperfusion (1)(2)(3)(4)(5)(6). The occurrence of VT/VF after thrombolysis has been shown to be associated with an increased risk of in-hospital and one-year adverse events (6).…”
Section: See Page 1788mentioning
confidence: 98%
See 1 more Smart Citation
“…19 This was further supported by the Thrombolysis In Myocardial Infarction II data (2546 patients). 20 In contrast, Gheeraert et al 21 recently reported that acute anterior MI caused by occlusion of the left coronary artery was associated with greater risk of primary VF compared with the right coronary artery, according to angiographic findings of 72 patients who survived out-of-hospital VF. In a more recent clinical trial (Collaborative Organization for RheothRx Evaluation [CORE] trial, with 2100 patients), the incidence of primary VF was higher in patients with acute inferior MI who had right ventricular involvement (8.4%) than in those with inferior MI without right ventricular involvement (2.7%) or anterior MI (5.0%).…”
Section: Yan Et Al Phase 2 Reentry In Acute Myocardial Ischemiamentioning
confidence: 98%
“…Of the patients 6.8% had nonsustained ventricular tachy cardia, which did not carry predictive information on 6-month mortality [26]. Correspondingly, the SPRINT study demontrated ventricular tachycardia, developing within 48 h of AMI and without simultaneous hemody namic compromise, to contain no predictive information on in-hospital clinical course or 1-year mortality [27], Studies combining sustained ventricular tachycardia and/ or ventricular fibrillation, developing within the first 48 h after AMI and without simultaneous heart failure, dem onstrated these arrhythmic variables to predict in-hospital and short-but not long-term mortality [28,29]. Ven tricular fibrillation accompanied by heart failure has also been demonstrated to be an independent predictor of high in-hospital mortality, but not of 5-year mortality [30], In agreement with these studies, the present study demon strated that ventricular tachycardia had no predictive implication on either short-or long-term mortality.…”
Section: Ventricular Tachycardia and Ventricular Fibrillationmentioning
confidence: 99%